Existence of Mild Solutions for Fuzzy Fractional Evolution Equations via Krasnosel’skii Fixed Point Theorem - Ismail Airou; Ali El Mfadel; Elomari Mhamed (Sahand Communications in Mathematical Analysis)
The primary purpose of this paper is to investigate the existence of two distinct types of fuzzy mild solutions for fuzzy fractional evolution equations under Caputo's $gH-$differentiability. The proofs are based on fuzzy strongly continuous semigroups, a new Krasnoselskii fixed point theorem appropriate for fuzzy metric spaces, and some elementary fuzzy fractional calculus tools.